2019
DOI: 10.21668/health.risk/2019.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Health Risks for Employable Population Caused by Food Products Contamination (Experience Gained in Samara Region)

Abstract: В настоящее время актуальной проблемой является обеспечение безопасности питания населения посредством проведения мероприятий по снижению риска неблагоприятного воздействия контаминантов на здоровье человека, в том числе через систему государственного санитарно-эпидемиологического надзора. По данным лаборатории ФБУЗ «Центр гигиены и эпидемиологии в Самарской области» проанализировано 71 204 пробы пищевых продуктов на содержание тяжелых металлов (кадмия, ртути, свинца, мышьяка), пестицидов (гексахлорцилогексана… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…At present, the research on environmental and health management is more extensive. The results of cluster analysis showed that the research directions of environmental and health management could be divided into seven different categories: soil pollution and health [3][4][5][6], water pollution and health [7][8][9][10][11], air pollution and health [12][13][14][15], food, medicine and health [16][17][18][19][20], indoor environment and health [21][22][23][24][25], urban environment and health [26][27][28][29][30], and environmental governance and health [31][32][33]. The research hotspots and frontiers in the field of environmental health problems mainly focused on indoor air pollution and control [34][35][36][37][38][39][40], treatment of schistosomiasis and veterinary drug residues [41][42][43][44][45][46], control and treatment of inhalable particulate matter in the atmosphere [47][48]…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research on environmental and health management is more extensive. The results of cluster analysis showed that the research directions of environmental and health management could be divided into seven different categories: soil pollution and health [3][4][5][6], water pollution and health [7][8][9][10][11], air pollution and health [12][13][14][15], food, medicine and health [16][17][18][19][20], indoor environment and health [21][22][23][24][25], urban environment and health [26][27][28][29][30], and environmental governance and health [31][32][33]. The research hotspots and frontiers in the field of environmental health problems mainly focused on indoor air pollution and control [34][35][36][37][38][39][40], treatment of schistosomiasis and veterinary drug residues [41][42][43][44][45][46], control and treatment of inhalable particulate matter in the atmosphere [47][48]…”
Section: Introductionmentioning
confidence: 99%
“…В ряде научных работ показано, что традиционные продукты массового потребления (зерновые и хлебобулочные изделия, молочные продукты, овощи, картофель) вносят наиболее значительный вклад в риски для здоровья, обусловленные содержанием в них токсичных элементов [7][8][9]. В продуктах растительного происхождения химические элементы находятся в ионной форме или связаны с растительным белком и пектином.…”
unclassified
“…Some studies have shown that traditional mass consumption products (cereals, bakery, milk products, vegetables, and potatoes) make the most considerable contributions to health risks caused by toxic elements in them [7][8][9]. Chemicals are usually contained in plant products in their ion form or are bound to a plant protein and pectin.…”
mentioning
confidence: 99%